2022
DOI: 10.17219/dmp/146038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an experimental chitosan/casein gel on demineralized enamel under a cariogenic challenge

Abstract: Background. Dental caries is considered one of the most common oral health diseases.Objectives. The aim of the study was to evaluate the effects of an experimental chitosan/casein gel on enamel demineralization/remineralization in an environment with a high cariogenic challenge. Material and methods.Thirty-six specimens of bovine enamel (4 mm × 3 mm × 2 mm) were ground flat and polished. Then, the specimens were immersed in acetate buffer for 43 h with half of the surface protected (serving as control) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Puangpanboot et al evaluated the effect of chitosan on the remineralisation and microhardness of enamel and found that the microhardness of enamel increased signi cantly following chitosan application [34].…”
Section: Evaluation Of Microhardnessmentioning
confidence: 99%
“…Puangpanboot et al evaluated the effect of chitosan on the remineralisation and microhardness of enamel and found that the microhardness of enamel increased signi cantly following chitosan application [34].…”
Section: Evaluation Of Microhardnessmentioning
confidence: 99%
“…Caries is considered one of the most prevalent chronic diseases in adults and children worldwide. Its multifactorial etiology characterizes it as a dysbiosis involving specific microorganisms, such as Streptococcus mutans , fermentable carbohydrates, dental surface, and exposure time 7–9 . The imbalance between the presence of cariogenic biofilms and the consumption of fermentable carbohydrates over time, 10 along with the cariogenic pathogen, plays a decisive role in caries development 11 …”
Section: Introductionmentioning
confidence: 99%
“…Its multifactorial etiology characterizes it as a dysbiosis involving specific microorganisms, such as Streptococcus mutans, fermentable carbohydrates, dental surface, and exposure time. [7][8][9] The imbalance between the presence of cariogenic biofilms and the consumption of fermentable carbohydrates over time, 10 along with the cariogenic pathogen, plays a decisive role in caries development. 11 All these factors and conditions contribute to the dynamic processes of demineralization and remineralization that occur on the dental surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the prevention and treatment of dental caries base on the following techniques: blocking or regulating the progression of dental caries by removing or managing the pathogens and restoring the balance of the oral microbiota; restoring the structure and function of teeth in response to the damage that caries has caused to their integrity (Cheng et al, 2022). Chitosan, as a relatively new natural polymer in dental applications (Yamakami et al, 2022), has been widely studied and confirmed for its anticaries effects, mainly through the development of anti-caries products or clinical adjuvant treatment technologies, such as antibacterial, biomimetic mineralization and dentin binding, anticaries drug delivery, with broad application prospects (Figure 1). As the first article we have learned about the anti-caries effect of chitosan, this article aims to provide a comprehensive overview of the anti-caries research of chitosan, summarize the research progress in the anti-caries mechanism of chitosan in recent years, and attempt to analyze the potential applications of chitosan in the future and the shortcomings of current research, providing theoretical reference for further researches and breakthroughs in chitosan anti-caries materials and clinical implementation.…”
Section: Introductionmentioning
confidence: 99%